The role of purchase interest in bridging service quality, E-WOM, and price perception toward purchase decisions: evidence from the Surakarta coffee shop industry - Muhammad Fajri Firdausi; Edy Purwo Saputro (Institute of Computer Science (IOCS), 2026)
This study examines the influence of service quality, electronic word of mouth (e-WOM), and price perception on coffee purchase decisions in Surakarta, with purchase intention serving as a mediating variable. The research problem arises from the limited understanding of how these three variables simultaneously affect purchasing decisions in the context of local coffee shops, particularly due to inconsistencies found in previous studies. This gap is significant as there is still a lack of research that integrates these variables into a comprehensive mediation framework within the coffee shop industry in Surakarta. The study employed a questionnaire-based survey involving 120 respondents who had prior purchasing experience at coffee shops. The data were analyzed using Structural Equation Modeling (SEM). The findings indicate that service quality and price perception have a positive and significant effect on both purchase intention and purchase decisions. Meanwhile, e-WOM positively influences purchase intention but does not have a direct effect on purchase decisions. Purchase intention acts as a mediating variable that strengthens the influence of service quality and price perception on purchase decisions. Theoretically, this study contributes to the development of marketing models by incorporating a mediation variable and emphasizing the role of purchase intention as a key linking mechanism. Practically, the results provide insights for coffee shop managers to focus on improving service quality, managing price perception, and optimizing the use of e-WOM to effectively enhance purchase intention and consumer purchasing decisions.